The State and Development Trends of The Conflict Between Ukraine and The Russian Federation - Qurbonov Arslonqul Amonovich (Indonesian Journal of Public Administration Review, 2025)
This article analyzes the current state of the conflict between Ukraine and the Russian Federation, as well as its impact on the geopolitical landscape and regional security in Central Asia. Special attention is given to the role of Uzbekistan in promoting stability and consolidating regional states amid contemporary geopolitical transformations